Application of the Workflow Mechanism in The Integrated Multilevel Information System of The Ministry of National Defence (IMISMND) On the Example of Selected Resource Management Processes - Maciej WIETRZYNSKI; Piotr JAKUBOWSKI; Rafal JANKOWIAK; Romuald HOFFMANN (Communications of International Proceedings, 2022)
The article presents two new solutions that have emerged as components of the entire IMISMND. The first example is the Process for Circulation of Protocols of Technical Status (PTS) as an integral part of the Operations Support Subsystem (OSS) of IMISMND. This process includes the logistics area. The second process analyzed is the processing of applications for departmental decorations, covering the HR area. The characteristics of the aforementioned processes are presented, detailing the key elements used at the design stage, followed by the implementation of solutions. In addition, an analysis of the effectiveness of the described processes is presented. The end of the article includes conclusions of the built solutions, along with their advantages and disadvantages, as well as activities related to the further development of IMISMND.
Keywords: workflow; SAP; ERP; Enterprise Resource Planning.